IDEAŁ WŁADCY I JEGO RODZINY NA PODSTAWIE MÓW POGRZEBOWYCH KU CZCI TEODOZJUSZA l, FLACYLLI I PULCHERII - Kamilla Twardowska (In Gremium. Studies in History, Culture and Politics, 2011)
THE PARAGON OF A RULER AND HIS FAMILY BASED ON THE FUNERALSPEECHES IN HONOUR OF THEODOSIUS I, FLACCILLA, AND PULCHERIATheodosius I is well known to historians. He was a great leader and a ruler, who made Christianity themain religion of the empire. Funeral speeches in his, his wife Flaccilla's and his daughter Pulcheria'shonor were created and are important sources in research concerning the changes in mentality andcustoms of people at the end of the 4th century.